Reformasi Pembelajaran Abad 21, Merdeka Belajar pada Anak Usia Dini Melalui Penggunaan Loose part: 21st Century Learning Reform, Freedom to Learn in Early Childhood Through the Use of Loose Parts - A. Tabi’in; Syifa Fauziah; Leli Fertiliana Dea; Arditya Prayogi (Universitas Ngudi Waluyo, 2024)
This research aims to determine the implementation of independent learning using loose part media in early childhood at KB Labschool UIN KH Abdurrahman Wahid Pekalongan. Freedom to play is a new learning concept that has a big opportunity to improve the quality of education in Indonesia. If the use of this learning model is carefully prepared, it will certainly have a significant impact on children's development. Through independent learning, children will be directed to have 21st century competencies, namely, communication, creativity, collaboration and critical thinking. Many PAUD schools have not implemented the concept of independent learning due to teachers' readiness to implement it. This research aims to determine the implementation of free play in early childhood through loose part media at KB Lab School UIN KH Abdurrahman Wahid Pekalongan. This research uses a descriptive qualitative method with a research focus on children's free play through loose part media. The primary data sources are school principals, educators and children. Data collection techniques use observation, interviews and documentation techniques. In checking the validity of the data using data triangulation. The results of the research show that the implementation of free play through loose parts for children at KB Lab School UIN KH Abdurrahman Wahid Pekalongan is that first the teacher prepares loose part media, second the children explore the materials that have been provided, third, the children are free to interact in building knowledge and empowering independence in activities learn how to teach. Apart from that, the benefits of implementing free play through loose part media are able to develop the 4c: creativity, communication, collaboration and critical thinking for children. ABSTRAK Penelitian ini bertujuan untuk mengetahui implementasi merdeka belajar menggunakan media loose part pada anak usia dini di KB Labschool UIN KH Abdurrahman Wahid Pekalongan. Merdeka bermain merupakan sebuah konsep pembelajaran baru yang berpeluang besar untuk meningkatkan kualitas pendidikan di Indonesia. Penggunaan model pembelajaran ini apabila dipersiapkan dengan matang tentunya akan berpengaruh secara signifikan bagi perkembangan anak. Melalui merdeka belajar anak akan diarahkan untuk memiliki kompetensi abad 21, yaitu, communication, creativity, collaboration, dan critical thingking. Banyak sekolah PAUD belum mengusung konsep merdeka belajar dengan alasan kesiapan guru dalam mengimplementasikannya. Penelitian ini bertujuan untuk mengetahui implementasi merdeka bermain pada anak usia dini melalui media loose part di KB Lab School UIN KH Abdurrahman Wahid Pekalongan. Penelitian ini menggunakan metode kualitatif deskriptif dengan fokus penelitian merdeka bermain pada anak melalui media loose part, adapun yang menjadi sumber data primer adalah kepala sekolah, pendidik dan anak-anak. Teknik pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Dalam pemeriksaan keabsahan data menggunakan tri angulasi data. Hasil penelitian menunjukkan bahwa implementasi merdeka bermain melalui loose part pada anak di KB Lab School UIN KH Abdurrahman Wahid Pekalongan yaitu pertama guru mempersipkan media loose part, kedua anak mengeksplorasi bahan yang sudah disediakan, ketiga, anak bebas berikteraksi dalam membangun pengetahuan dan pemberdayaan kemandirian dalam kegiatan belajar mengajar. Selain itu dari manfaat pelaksanaan merdeka bermain melalui media loose part tersebut mampu mengembangkan 4c: creativity, communication, collaboration and critical thingking bagi anak-anak.